Strip intercropping with local crops increased Aconitum carmichaeli yield and soil quality - Liu, Chen; Yan, Pengdong; Liu, Zhenyu; Zhang, Jianglan; Zhang, Guoyan; Cui, Langjun (Frontiers in Plant Science, 2023)
Aconitum carmichaeli Debx. is a traditional Chinese medicine that is cultivated in China and Japan. However, the monoculturing of this herb substantially decreases soil quality. A comparative study on the soil environmental characteristics, herb growth and quality of A. carmichaeli intercropping with five local crops in two different areas was conducted. Herb growth and quality, including biomass and secondary metabolites, and rhizosphere soil environmental characteristics were measured. The results showed that the intercropping with the five local crops substantially improved the A. carmichaeli biomass and polysaccharide content, decreased the disease index, and altered three monoester diterpenoid alkaloids and three diester diterpenoid alkaloids accumulations. The intercrops also increased the soil pH, nitrogen-cycling-gene abundances, and potentially beneficial microorganism abundances, and it also changed the soil nutrient levels. Moreover, these intercropping patterns could alleviate the continuous cropping obstacles of A. carmichaeli. According to a comprehensive evaluation of the A. carmichaeli growth and quality, as well as the soil quality, the best intercropping systems were the A. carmichaeli intercropping with rice, maize, and peanut. In summary, the strip-intercropping systems could improve the A. carmichaeli growth and soil quality, and be beneficial to the sustainable ecological planting of A. carmichaeli.